G Agri Pack PLC & Mr. Getahun Asfaw V. Ethiopian Customs and Revenue Authority;Ethiopian Intellectual Property Office V. Tibebe Ayele, Federal Supreme Court Cassation - Birhanu, Alebachew (Bahir Dar University Journal of Law, 2022)
á‹¨á‰°áˆ˜áˆ¨áŒ¡ ááˆá‹¶á‰½